Assessment of the Influence of Formation Conditions of Embankments and Spoil Heaps on Their Stability When Dumped on Clay-Salt Slurries - Maxim Karasev; Tatsiana Astapenka (Eng)
The formation of geotechnical structures on foundations composed of low-strength soils is associated with a number of risks and difficulties. Soils such as clay-salt slurries are characterized by low bearing capacity and a tendency to deform under load. In this study, a numerical simulation of the stability analysis of an embankment constructed on low-strength soils consisting of clay-salt slurries is carried out, and the study of the dependence of the stability and behavior of the embankment on the configuration of this foundation, without taking into account the embedment of rocks and with introduction of rocks into the geotechnical system, is considered. The results prove that the sloping configuration of low-strength soils greatly complicates the stability of the embankment. It is noted that the stability factor is significantly reduced under the influence of loads on low-strength soil, particularly when the geotechnical system has a configuration with slope angles of 5° and 10°, and, in addition, when rocks are embedded in low-strength soil if the underlying soil layer is a weak foundation. In view of this, the assessment of embankment stability on clay-salt slurries requires careful analysis due to a number of specific characteristics of these soils that create complex geotechnical conditions.